1997
DOI: 10.1016/s1074-5521(97)90073-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based design and combinatorial chemistry yield low nanomolar inhibitors of cathepsin D

Abstract: The success of these studies clearly demonstrates the power of coupling the complementary methods of combinatorial chemistry and structure-based design. We anticipate that the general approaches described here will be successful for other members of the aspartyl protease class and for many other enzyme classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 31 publications
3
106
0
2
Order By: Relevance
“…If we imagine that on the order of 0.1% of a diverse database might have activity for a given target, then to have more than a handful of hits in the top 0.5% of a database of the size used here would require an enrichment factor of around 20-fold, which is typically considered a good improvement over random selection. 32 With an enrichment of 20-fold, one could expect 10 hits in the top 500 compounds, such that there is a 2% chance that a given compound is active. In an academic lab, one might reasonably test 20 to 50 compounds; even with a 20-fold enrichment, the chance that all 20 compounds are inactive is still 67%; for 50 compounds tested, the chance that all are inactive is 36%.…”
Section: Discussionmentioning
confidence: 99%
“…If we imagine that on the order of 0.1% of a diverse database might have activity for a given target, then to have more than a handful of hits in the top 0.5% of a database of the size used here would require an enrichment factor of around 20-fold, which is typically considered a good improvement over random selection. 32 With an enrichment of 20-fold, one could expect 10 hits in the top 500 compounds, such that there is a 2% chance that a given compound is active. In an academic lab, one might reasonably test 20 to 50 compounds; even with a 20-fold enrichment, the chance that all 20 compounds are inactive is still 67%; for 50 compounds tested, the chance that all are inactive is 36%.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are now appearing in the literature (Brown andMartin, 1996, 1997;Matter, 1997;Patterson et al, 1996) but only that by Snarey et al (1998) has provided a detailed analysis of some of the dissimilarity-based selection methods considered in this paper. More importantly, the full value of methods for analysis molecular diversity will only be obtained when they are linked to other, existing approaches to computer-aided molecular design, such as ligand docking, pharmacophore mapping and quantitative structure-activity relationships (Martin and Willett, 1998): the merits of such linked approaches are well illustrated by very recent work on the docking of combinatorial libraries (Jones et al, 1999;Kick et al, 1997), and we can expect many further such reports in the next few years.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethylenastron was docked onto the coordinates obtained from the crystal structure of Eg5 [18] , using standard DOCK methodology [19] . The lowest-energy Eg5/dimethylenastron interaction model was presented.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Dimethylenastron was docked onto the coordinates obtained from the crystal structure of Eg5 [18] , using standard DOCK methodology [19] , and the lowest-energy Eg5/ dimethylenastron interaction model was presented ( Figure 5A). Detailed analysis revealed that dimethylenastron binds to the motor domain of Eg5 in a pocket close to the ATP/ADP binding pocket on Eg5; there exist a loop (E116-R119) and an α-helix (G110-F113) between the two binding pockets ( Figure 5B).…”
Section: Dimethylenastron Allosterically Inhibits the Motor Domain Atmentioning
confidence: 99%